Inhibition of salivary amylase by black tea in high-caries and low-caries index children: A comparative in vivo study - Arya, Vishal (Ayu, 2015)
INTRODUCTION: Dental caries is a universal disease. Dietary modification is important in reducing the occurrence of dental caries. Tea which is so frequently consumed with cariogenic starch rich food is proposed to have anticariogenic potential. The various mechanism has been proposed for same and one being inhibition of salivary amylase activity. AIM: To determine the effect of 1.5% black tea decoction on salivary amylase activity in children with high caries and no caries. MATERIALS AND METHODS: A total of 30 children in the age group of 12–15 years were selected for the study. They were further grouped based on their decayed missing filled surface (DMFS) score into high-caries group (DMFS above 10) and no-caries group (DMFS = 0). After 2 h of fasting, subjects consumed two salted crackers for 60 s following which they rinsed with water and then with black tea decoction (1.5%) the very next day. Retained food particles were recovered salivary amylase activity was noted as maltose to sucrose ratio via chromatography. RESULTS: The average ratio of maltose to sucrose ratio percentage reduction in high-caries group was 43.63% and 41.17% in no caries group which was highly significant (P < 0.005) while the intergroup comparison was found statistically insignificant. CONCLUSIONS: Tea decoction has inhibitory effect on salivary amylase activity thus dental caries. The effect was statistically insignificant in children with high- and no-caries index.